Phenytoin Topical as Pain Neuropathic Therapy: A Scoping Review - Sulistyani, S; Rosyidah, Devi Usdiana; Rahmawati, Nailena Widya; Nugrahaen, Sarwasri Fajra; Goprani, Lidya; Sulistiyo, Azka Hafiy; Prameswari, Elza; Hutami, Norma Putri; Azwar, Muhammad Thoriq; Amalia, Riza (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2024)
Background: Neuropathic pain is a type of pain that can cause prolonged pain in patients. Oral treatment takes a long time and can cause side effects, which can further reduce patient compliance with therapy. Topical treatment is a more acceptable alternative because it has minimal systemic side effects. Phenytoin is an anticonvulsant drug that can be used as a therapy for neuropathic pain. The side effects of oral phenytoin are minimized by using topical preparations. Objective: To obtain information on the effectiveness of topical phenytoin in neuropathic pain. Long-term goal, conduct clinical trials in patients and make topical phenytoin preparations in collaboration with one of the PBF (Large Pharmaceutical Companies) in Indonesia. Methods: Three electronic databases were searched on January 13, 2022: Google Scholar. PubMed and ScienceDirect. All relevant literature was included after screening according to the PRISMA statement. Data obtained were synthesized based on PICO (population, interventions, comparisons, and outcomes). Results: This paper examines case reports, case series, and pre-existing research articles in which topical phenytoin significantly reduces neuropathic pain. Conclusion: Topical phenytoin may be an alternative in the selection of neuropathic pain therapy due to its minimal side effects compared to oral therapy. However, further studies need to be conducted to compare with other topical anticonvulsants.